VO#01: Approval of unit rate for applying emulsion paint on ceiling and enamel paint - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the approval of unit rate for applying emulsion paint on ceiling and enamel paint for BRACU new campus project.